Odpowiedzi

2010-04-07T14:00:42+02:00
A)
10=4-2x
2x=4-10
2x=-6
x=-3

b)
-(2x-1)=4
-2x+1=4
-2x=4-1
-2x=3
x=-3/2

c)
2(x+1)=x
2x+2=x
2x-x=-2
x=-2

d)
2t-(3t+1)=6
2t-3t-1=6
-t=6+1
-t=7
t=-7

e)
-(4+x)=2(3-x)
-4-x=6-2x
-x+2x=6+4
x=10

f)
1-0,2x=-0,3x
-0,2x+0,3x=-1
0,1x=-1
x=-10

g)
0,01-1=0,1x-0,1
-0,1x=-0,1-0,01+1
-0,1x=1,11
x=-0,111
Najlepsza Odpowiedź!
  • 8650
  • Rozwiązujący
2010-04-07T14:01:23+02:00
10=4-2x
2x=4-10
2x=-6 //:2
x=-3

-(2x-1)=4
-2x+1=4
-2x=4-1
-2x=3 //:(-2)
x=-1,5

2(x+1)=x
2x+2=x
2x-x=-2
x=-2

2t-(3t+1)=6
2t-3t-1=6
-t-1=6
-t=6+1
-t=7 //:(-1)
t=-7

-(4+x)=2(3-x)
-4-x=6-2x
-x+2x=6+4
x=10

1-0,2x=-0,3x
-0,2x+0,3x=-1
0,1x=-1 //:0,1
x=-10

0,01-1=0,1x-0,1
-0,1x=-0,1-0,01+1
-0,1x=0,89 //:(-0,1)
x=-8,9